'To the great public': The Architectural Image in the Early Illustrated London News. Issue 1 (28th December 2017) - Hultzsch, Anne
Abstract : The Illustrated London News, launched in May 1842 as the first illustrated newspaper and quickly copied across Europe, North America and beyond, was full of architectural images. New buildings, ancient ruins, construction sites, royal visits, wars, theatre performances, exotic expeditions, historical essays and innumerable other subjects gave occasion to feature the built, whether for its own sake or as background setting. Images and texts were produced and consumed with an urge and at a speed never seen before. The building, through the illustrated press, left the static confines of the book and the framed print and became peopled by the purposeful bourgeoisie. Through a close analysis of a range of articles on the new Royal Exchange, the refurbished London Colosseum as well as the Queen's Scotland tour, this essay explores the role of the architectural image in the illustrated press by focusing on its relationship to the accompanying text. Untangling the mechanics of representation and perception, it identifies modes of intellectual, affective, and kinetic vision through which architecture was represented to the remote reading public. By externalising and stabilising vision, the Illustrated London News thus created a virtual public sphere in which the dramatic technological and material changes occurring in the period could be absorbed and normalized.